Improving Students’ Reading Comprehension by Using CIRC (Cooperative Integrated Reading and Composition) - Rochyani Lestiyanawati (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2022)
The reading competence of Indonesian students is unsatisfactory caused by the inappropriate teaching technique. Reading is a complex cognitive activity so that it needs an appropriate technique in teaching. The objective of this study is to measure the use of Cooperative Integrated Reading and Composition (CIRC) technique to improve students’ reading comprehension. The subject of the study were 35 numbers of 11th graders of vocational school students. The findings showed that the average of the pre-test and post-test scores were 67.4 and 88.03 .The improvement calculation was found 0.632 which was categorized as medium. The calculation of applying the t-test was on rejection area of ​​Ho, showed that the post-test was better than the pre-test. According to the data analysis, the researcher concluded that teaching reading by using CIRC technique is applicable since it helps the students to improve their reading comprehension.